HUBUNGAN ANTARA KONSUMSI EMPING MELINJO DENGAN KEJADIAN ASAM URAT PADA WARGA DI DESA WADUNGGETAS WONOSARI KLATEN - Ariasti, Dinar; Lestari, Wiji (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background:Uric acid is always present in the human body, when the rising levels (hyperuricemia) can cause complaints gouty arthritis. The cause of gout arthritis varies and is triggered by a diet high in purine. One diet high in purine include mlinjo (Gnetum gnemon linn) because it contains 50-150 mg of purines per 100 g of beans melinjo, with one of the forms are processed emping melinjo. Results of preliminary observations most people are less concerned with what they eat everyday including emping melinjo consumed as a snack when relaxing. They did not know that eating emping could lead to an increased risk of gout.The purpose of this study was to determine the relationship between the consumption of emping melinjo with the incidence of gout in Wonosari Wadunggetas residents in the village of Klaten.The subjects were Wadunggetas Wonosari Klaten village residents over the age of 40 years a number of 30 respondents. The samples was conducted with a saturated sampling technique, namely by taking all members of the population being sampled because the population is small.Methods in this study isanalytical research design correlation to determine the relationship of chips melinjo consumption as independent variables (independent variable) and the incidence of gout as the dependent variable (dependent variable). Data obtained by questionnaire and observation method. The data collected is then analyzed with chi square test with Î± 0.05.The results of the study there were 9 respondents with the level of consumption of chips often, all experienced gout, 14 respondents with a rare level of consumption of chips, 11 experienced gout and 3 are not experiencing gout and 7 respondents who do not eat emping no suffer from gout. After Chi-Square test with SPSS version 16.0 with Î± = 5% (0:05) so obtained p 0.000 p value of <0.05, which means that Ho is rejected and Ha accepted.The conclusion of this study is that there is a relationship between the level of consumption of emping melinjo with the incidence of gout in the village Wadunggetas Wonosari Klaten.Keywords: Emping Mlinjo Comsumtion and Gout Disease